2013
DOI: 10.1371/journal.pone.0073485
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Propensity Is Increased under Atrial Fibrillation Hemodynamics: A Simulation Study

Abstract: Atrial fibrillation (AF) is the most common sustained dysfunction in heart rhythm clinically and has been identified as an independent risk factor for stroke through formation and embolization of thrombi. AF is associated with reduced cardiac output and short and irregular cardiac cycle length. Although the effect of AF on cardiac hemodynamic parameters has been reported, it remains unclear how the hemodynamic perturbations affect the potential embolization of blood clots to the brain that can cause stroke. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…In other words, elevated stroke propensity by AF was shown to be evident in some of the aortic configurations (Fig. 4A ) which is consistent in our previous observation 17 while such pattern was not observed in other aortic structures (Fig. 4B ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In other words, elevated stroke propensity by AF was shown to be evident in some of the aortic configurations (Fig. 4A ) which is consistent in our previous observation 17 while such pattern was not observed in other aortic structures (Fig. 4B ).…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously demonstrated that the motion of a blood clot in blood flow is multifaceted such that the trajectory of a clot is governed by the interplay between hemodynamics and clot properties 17 . Despite such complexities, however, the simulations show that pressure gradient force can be a dominant factor that determines the trajectory of a clot and thus affects the stroke propensity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have used biophysical modeling and simulation to investigate how hemodynamic perturbations affect the potential embolization of blood clots that ultimately cause stroke. Results suggest that these reduce cardiac output and cycle length induced by AF can significant increase incidence of embolism (Choi et al 2013). The same group recently extended their work to simulate a stroke-prevention device designed to deflect a blood clot.…”
Section: Research Horizonsmentioning
confidence: 99%